Hematopoietic progenitor cell mobilization is more robust in healthy African American compared to Caucasian donors and is not affected by the presence of sickle cell trait. Issue 5 (May 2016) - Panch, Sandhya R.; Yau, Yu Ying; Fitzhugh, Courtney D.; Hsieh, Matthew M.; Tisdale, John F.; Leitman, Susan F.
Abstract : BACKGROUND: Granulocyte–colony‐stimulating factor (G‐CSF)‐stimulated hematopoietic progenitor cells (HPCs) collected by apheresis have become the predominant graft source for HPC transplantation in adults. Among healthy allogeneic donors, demographic characteristics (age, sex, body mass index [BMI]) and baseline hematologic counts affect HPC mobilization, leading to variability in CD34+ apheresis yields. Racial differences in HPC mobilization are less well characterized. STUDY DESIGN AND METHODS: We retrospectively analyzed data from 1096 consecutive G‐CSF–stimulated leukapheresis procedures in healthy allogeneic African American (AA) or Caucasian donors. RESULTS: In a multivariate analysis, after adjusting for age, sex, BMI, baseline platelet and mononuclear cell counts, and daily G‐CSF dose, peak CD34+ cell mobilization was significantly higher among AAs (n = 215) than Caucasians (n = 881; 123 ± 87 × 10 6 cells/L vs. 75 ± 47 × 10 6 cells/L; p < 0.0001). A ceiling effect was observed with increasing G‐CSF dose (10 µg/kg/day vs. 16 µg/kg/day) in AAs (123 ± 88 × 10 6 cells/L vs. 123 ± 87 × 10 6 cells/L) but not in Caucasians (74 ± 46 × 10 6 cells/L vs. 93 ± 53 × 10 6 cells/L; p < 0.001). In AA donors, the presence of sickle cell trait (SCT; n = 41) did not affect CD34+ mobilization (peak CD34+ 123 ± 91 × 10 6 cells/L vs. 107 ± 72 × 10 6 cells/L, HbAS vs. HbAA; p = 0.34). Adverse events were minimal and similar across race. CONCLUSIONS: AAs demonstrated significantly better CD34 mobilization responses to G‐CSF than Caucasians. This was independent of other demographic and hematologic variables. Studying race‐associated pharmacogenomics in relation to G‐CSF may improve dosing strategies. Adverse event profile and CD34 mobilization were similar in AA donors with and without SCT. Our findings suggest that it would be safe to include healthy AA donors with SCT in unrelated donor registries.